Reforms on retirement and other changes in the Social Security System (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
Law 3/2012, LMURML and, above all, the Royal Decree-Law 20/2012, labor reform and fiscal adjustment-introduce powerful modifications and consequences in the Spanish social security system. Among these many reforms we emphasize the modification of the system of compulsory retirement, which imposes the nullity of clauses of collective agreement sproviding for the termination of work to meet the worker’s normal retirement age.This article also discusses the important settings and controls imposed on unemployment benefits or protection to public officials, among other measures.
Keywords: Social Security; Retirement; Unemployment; Officials; Temporary disability; Dependence; Collective bargaining agreement.